ECO – INNOVATIVE CARBURIZING: ENHANCING STEEL ST 37 WITH ALABAN CHARCOAL AND EGGSHELL CATALYSTS - Ahmad Robittah; Suprapto, Wahyono; Widodo, Teguh Dwi; Wirawan , Willy Artha; Sabitah, A’yan (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2025)
This study examines the enhancement of St 37 steel through an eco-friendly carburization process using Alaban charcoal and eggshell catalyst. The agriculture sector in South Kalimantan, Indonesia, depends largely on metal tools made from low-carbon steel, which need greater hardness and durability. Traditional carburization techniques are costly and often lead to uneven carbon distribution. This research investigates the use of Alaban wood charcoal and local duck eggshell waste as carburizing agents. The experiment involved varying the weight ratio of charcoal to eggshell powder, then carburizing at 950°C for two hours, followed by water quenching. The results indicated a notable increase in surface carbon content, diffusion depth, hardness, and microstructure of St 37 steel. The optimal combination, achieving the highest surface hardness of 947 HV and a carbon diffusion depth of 1.0 mm, was found at an eggshell catalyst concentration of 30%. All samples exhibited a microstructural change to martensite. These results demonstrate the potential of using agricultural waste to enhance steel properties, promoting more sustainable and cost-effective industrial practices.